Analisis Pengaruh “Return On Equity, Current Ratio”, Price Earning Ratio , “Debt To Equity Ratio” Dan “Total Asset Turnover” Terhadap Return Saham - Muhamad Ory Adrianto; Sugianto Sugianto (Jurnal Publikasi Ilmu Manajemen, 2023)
Returnis one of the factors that motivates investors to engage and also is a reward for the courage of investors in taking risks on the investments they make. The purpose of this study is to determine the effect“Return on Equity”,“Current Ratio”,price earning ratio,“Debt to Equity Ratio” and total assets turnover on stock returns in companies included in the LQ-45 index on the Indonesia Stock Exchange in the 2016-2021 period. The population in this study are companies on the Indonesia Stock Exchange in the 2016-2021 period. The sampling technique in this study used purposive sampling. Empirical findings prove that the NPL ratio factors affect firm value, while other factors namely; Company growth (FG), CAR, Loans (LDR), BOPO, DPK Growth (DG) and profitability partially do not affect the value of the company (Tobin's Q), but affect the value of the company (Tobin's Q) together.